An Increase in Plasma Homovanillic Acid with Cocoa Extract Consumption Is Associated with the Alleviation of Depressive Symptoms in Overweight or Obese Adults on an Energy Restricted Diet in a Randomized Controlled Trial. Issue 4 (9th March 2016) - Ibero-Baraibar, Idoia; Perez-Cornago, Aurora; Ramirez, Maria J; Martínez, J Alfredo; Zulet, M Angeles
Abstract: Background: Obesity has been associated with various health disorders, including psychological alterations. Cocoa consumption and weight management may produce a beneficial effect on these problems. Objective: The purpose of this study was to investigate the effect of cocoa extract supplementation as part of an energy-restricted diet on psychological status and peripheral dopaminergic activity in overweight or obese middle-aged subjects. Methods: In a 4-wk, double-blind, randomized, placebo-controlled parallel nutritional intervention, 22 men and 25 women [mean ± SD age: 57 ± 5 y; body mass index (kg/m 2 ): 30.6 ± 2.3] were studied. After a 1-wk run-in period, volunteers consumed 15% energy-restricted diets; one-half of the volunteers were randomly assigned to receive ready-to-eat meals supplemented with 1.4 g cocoa extract/d (645 mg total polyphenols/d), whereas the rest of the volunteers received the same meals without cocoa supplementation. Plasma monoamines [dopamine, dopac, and homovanillic acid (HVA)], monoamine oxidase (MAO), and psychological status (anxiety and depressive symptoms) were analyzed in fasting participants at baseline and endpoint. Data were analyzed over time, and regression and correlation analyses were conducted to determine the relation between variables. Results: Depressive symptoms decreased in both groups after the intervention (control: −9.4%, P < 0.001; cocoa: −6.3%, P = 0.008), but anxiety symptoms did not. The increase in plasma HVA was 11.5% greater in the cocoa group than in the control group ( P = 0.016), but plasma dopamine, dopac, and MAO changes did not differ between groups. A negative relation between changes in depressive symptoms and changes in plasma HVA was observed in the cocoa group (β = −0.39, P = 0.029). Moreover, the change in plasma dopamine was positively associated with the change in methyl-catechin- O -glucoronide in the cocoa-supplemented group ( r = 0.69, P = 0.019). Conclusion: The intake of cocoa extract by participants consuming a 15% energy-restricted diet contributed to an increase in plasma HVA concentrations. This change was associated with a reduction in depressive symptoms, suggesting a potential effect of cocoa extract intake on this relation. The present results are secondary analyses of a clinical trial that was registered at www.clinicaltrials.gov as NCT01596309.